Fatal Delayed Hemorrhage after Endoscopic Sphincterotomy Associated with Rivaroxaban: A Forensic Case Report - Siyeon Kim; Seon Jung Jang (Korean Journal of Legal Medicine, 2026)
A 78-year-old man with a history of cerebral infarction developed fatal delayed hemorrhage after endoscopic sphincterotomy while receiving rivaroxaban. Anticoagulation therapy was withheld only on the morning of the procedure. The duration for which therapy was withheld was shorter than that recommended in guidelines, reflecting the urgency of concurrent cholangitis requiring prompt biliary drainage. The patient developed recurrent hematemesis with a gradual decrease in hemoglobin level after the procedure; however, his vital signs remained stable. Rivaroxaban was resumed approximately 48 hours later on this basis, without further confirmation of hemostasis. Within 6 hours, the patient’s hemoglobin level dropped sharply, and massive hemorrhage led to cardiac arrest and death. The findings in this case are not aimed at questioning individual clinical decisions, but rather at showing that vital signs alone may not reflect ongoing hemorrhage during compensated blood loss, making “adequate hemostasis” difficult to confirm in practice and suggesting that in older patients with multiple risk factors, this ambiguity can prove fatal.